Move analysis the structure of narrative essays by Thai undergraduate students: A genre-based approach - Prachanant, Nawamin; Pongpuehee, Sittisak (Edelweiss Applied Science and Technology, 2025)
This study aimed to 1) analyze the moves/steps of the narrative essays written by the students of the English Program under the Faculty of Humanities and Social Sciences at Buriram Rajabhat University, and 2) identify the moves/steps that are obligatory or optional in the narrative essays written by the students of the English Program under the Faculty of Humanities and Social Sciences at Buriram Rajabhat University. Grounded in a genre-based approach, the study employed a mixed-method research design. A total of 34 narrative essays written by English major students at Buriram Rajabhat University were purposively selected and analyzed using Swales’ genre analysis framework and Labov and Waletzky [1] Personal Experience Narrative (PEN) model. Quantitative analysis determined the frequency and classification of rhetorical moves, while qualitative interpretation explored the narrative functions of each move and step. The results identified eight obligatory steps that commonly occurred, including announcing the beginning of the story, introducing characters and settings, recapitulating events, resolving tension, and concluding with reflections. Other steps were found to be optional and varied across the corpus. The study concluded that Thai undergraduate students generally followed a culturally consistent rhetorical structure in their narrative essays. Educators should teach rhetorical moves and their narrative significance explicitly to students to improve their academic writing abilities. The study proposes additional research to examine how social culture affects narrative structure and to analyze differences in narrative writing preferences between cultures.